A novel economic analysis on multiterminal VSC HVDC systems with wind farms by hierarchical small‐signal stability constrained OPF. Issue 4 (2nd January 2020) - Kim, Sangwon; Yokoyama, Akihiko; Takaguchi, Yusuke; Takano, Tomihiro; Mori, Kazuyuki; Izui, Yoshio
Abstract : In this paper, a novel economic analysis for multiterminal voltage‐source converter high‐voltage direct current (MTDC) systems with wind farms is developed. Both the reinforcement and operation methods of an MTDC system are determined hierarchically in the proposed approach. Based on these methods, not only wind power transmission but also the MTDC system is capable of contributing to the power transmission among alternating current (AC) grids in cases of low wind power production cases. As a consequence, the economic benefits produced by the MTDC system can be increased. This paper also focuses on the sensitivity analysis of small‐signal stability constraints on the developed approach. It is demonstrated that the system for wind power transmission without any MTDC systems is exposed to instability, which is solved by the proposed method. On top of that, the small‐signal stability improvement effect of the MTDC system is analyzed from the economic viewpoint. Under strict small‐signal stability constraints, the economic benefits obtained by the MTDC system increase. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.